Addressing gender and social dynamics to strengthen resilience for all - Theis, Sophie; Bryan, Elizabeth; Ringler, Claudia (International Food Policy Research Institute, 2019)
2019 ReSAKSS Annual Trends and Outlook Report 127 In the face of various social, economic, health, political, and environmental risks, resource-poor people and communities in rural Africa employ diverse livelihood strategies to avoid, cope with, and adapt to multiple shocks and stressors. The African continent faces severe challenges related to increasing temperatures, water stress, and environmental degradation (Niang et al. 2014), and climate change exacerbates the risks posed by other threats such as rapid population growth, haphazard urbanization, conflict, extreme poverty, food and nutrition insecurity, public health threats, and corruption. In recognition of this confluence of risks and the diverse strategies people use to manage risk, the concept of resilience has taken hold in humanitarian and development communities as a unifying framework for identifying and planning for multiple, simultaneous risks that threaten rural people’s well-being. In addition, a resilience lens widens the time frame for considering risks. In so doing, it helps focus attention on the implications of humanitarian interventions on longer-term development and on safeguarding development gains against shocks, thereby helping to bridge the humanitarian and development sectors (Frankenberger et al. 2014; Béné et al. 2016).